LITE SABR M1: A phase I trial of Lattice stereotactic body radiotherapy for large tumors. (February 2022) - Duriseti, Sai; Kavanaugh, James A.; Szymanski, Jeff; Huang, Yi; Basarabescu, Franco; Chaudhuri, Aadel; Henke, Lauren; Samson, Pamela; Lin, Alexander; Robinson, Clifford; Spraker, Matthew B.
Highlights: Lattice SBRT is a safe palliative treatment for large tumors. Lattice SBRT did not worsen patient reported toxicity or quality of life. Lattice SBRT is associated with substantial tumor shrinkage. Lattice SBRT induces changes in cytokine/chemokine levels. Abstract: Purpose: Stereotactic body radiotherapy (SBRT) is an attractive treatment option for patients with metastatic and/or unresectable tumors, however its use is limited to smaller tumors. Lattice is a form of spatially fractionated radiotherapy that may allow safe delivery of ablative doses to bulky tumors. We previously described Lattice SBRT, which delivers 20 Gy in 5 fractions with a simultaneous integrated boost to 66.7 Gy in a defined geometric arrangement (Lattice boost). The goal of this study was to prospectively evaluate the acute toxicity and quality of life (QoL) of patients with large tumors (>5 cm) treated with Lattice SBRT. Methods: This was a single-arm phase I trial conducted between October 2019 and August 2020. Patients with tumors > 4.5 cm were eligible. Lattice SBRT was delivered every other day. The primary outcome was the rate of 90-day treatment-associated (probably or definitely attributable) grade 3 + acute toxicity by Common Terminology Criteria for Adverse Events (CTCAE) version 5.0 criteria. Other outcomes included changes in patient reported toxicity and QoL inventories, GTV, and peripheral blood cytokines. Results: Twenty patients (22 tumors) were enrolled. Median GTV was 579.2 cc (range: 54.2–3713.5 cc) in volume and 11.1 cm (range: 5.6–21.4 cm) in greatest axial diameter. Fifty percent of tumors were in the thorax, 45% abdomen/pelvis, and 5% extremity. There was no likely treatment-associated grade 3 + toxicity in the 90-day period (acute and sub-acute). There was one case of grade 4 toxicity possibly associated with Lattice SBRT. Conclusions: This phase I study met its primary endpoint of physician reported short-term safety. An ongoing phase II clinical trial of Lattice SBRT will evaluate late safety and efficacy of this novel technique.